The macroeconomic effects of fiscal policy - António Afonso; Ricardo M. Sousa (European Central Bank (ECB), 2009)
We investigate the macroeconomic effects of fiscal policy using a Bayesian Structural Vector Autoregression approach. We build on a recursive identification scheme, but we: (i) include the feedback from government debt (ii); look at the impact on the composition of output; (iii) assess the effects on asset markets (via housing and stock prices); (iv) add the exchange rate; (v) assess potential interactions between fiscal and monetary policy; (vi) use quarterly data, particularly, fiscal data; and (vii) analyze empirical evidence from the U.S., the U.K., Germany, and Italy. The results show that government spending shocks, in general, have a small effect on GDP; lead to important “crowding-out” effects; have a varied impact on housing prices and generate a quick fall in stock prices; and lead to a depreciation of the real effective exchange rate. Government revenue shocks generate a small and positive effect on both housing prices and stock prices that later mean reverts; and lead to an appreciation of the real effective exchange rate. The empirical evidence also shows that it is important to explicitly consider the government debt dynamics in the model.
Keywords: C11; C32; E62; H62; 330; Bayesian Structural VAR; debt dynamics; Fiscal Policy; Finanzpolitik; Öffentliche Schulden; Wirkungsanalyse; Bayes-Statistik; VAR-Modell; Deutschland; Großbritannien; Italien; USA